2023
DOI: 10.1177/10815589221149189
|View full text |Cite
|
Sign up to set email alerts
|

Hematological ratios in coronavirus disease 2019 patients with and without invasive mechanical ventilation

Abstract: Patients with the most severe form of coronavirus disease 2019 (COVID-19) often require invasive ventilation. Determining the best moment to intubate a COVID-19 patient is complex decision and can result in important consequences for the patient. Therefore, markers that could aid in clinical decision-making such as hematological indices are highly useful. These markers are easy to calculate, do not generate extra costs for the laboratory, and are readily implemented in routine practice. Thus, this study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The study design was prospective in three studies ( 50 , 67 , 68 ), unclear in one ( 66 ), and retrospective in the remaining 36 ( 21 , 36 49 , 51 65 , 69 74 ). The clinical endpoints included mortality in 19 studies ( 36 , 37 , 39 , 41 , 43 , 45 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 61 , 65 , 66 , 68 , 73 ), and measures of severe disease as follows: disease severity based on existing guidelines in eight ( 42 , 44 , 63 , 64 , 67 , 70 , 72 , 74 ), transfer to the intensive care unit (ICU) in eight ( 38 , 40 , 45 , 50 , 53 , 62 , 68 , 69 ), invasive mechanical ventilation in two ( 46 , 52 ), disease progression in two ( 57 , 71 ), prolonged hospital stay in one ( 21 ), intubation in one ( 37 ), deep vein thrombosis in one ( 54 ), acute pulmonary embolism in one ( 54 ), and acute limb ischemia in one ( 39 ). All studies reported the SII on hospital admission.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study design was prospective in three studies ( 50 , 67 , 68 ), unclear in one ( 66 ), and retrospective in the remaining 36 ( 21 , 36 49 , 51 65 , 69 74 ). The clinical endpoints included mortality in 19 studies ( 36 , 37 , 39 , 41 , 43 , 45 , 48 , 49 , 51 , 52 , 55 , 56 , 58 , 60 , 61 , 65 , 66 , 68 , 73 ), and measures of severe disease as follows: disease severity based on existing guidelines in eight ( 42 , 44 , 63 , 64 , 67 , 70 , 72 , 74 ), transfer to the intensive care unit (ICU) in eight ( 38 , 40 , 45 , 50 , 53 , 62 , 68 , 69 ), invasive mechanical ventilation in two ( 46 , 52 ), disease progression in two ( 57 , 71 ), prolonged hospital stay in one ( 21 ), intubation in one ( 37 ), deep vein thrombosis in one ( 54 ), acute pulmonary embolism in one ( 54 ), and acute limb ischemia in one ( 39 ). All studies reported the SII on hospital admission.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-nine studies (with 45 patient groups) reported the SII in 19,352 patients (mean age 61 years, 55% males) with a non-severe disease/survivor status and 5,524 patients (mean age 69 years, 60% males) with a severe disease/non-survivor status. Twenty-three studies were conducted in Asia ( 36 , 38 , 40 42 , 48 51 , 57 , 59 , 62 68 , 70 74 ), eleven in Europe ( 21 , 39 , 43 , 44 , 47 , 55 , 56 , 58 , 60 , 61 , 69 ), four in America ( 37 , 45 , 46 , 52 ), and one in Africa ( 53 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR is also studied as a predictive biomarker in COVID-19 ( 70 72 ): Fernandes et al ( 73 ) found that NLR levels are higher in COVID-19 patients who needed invasive mechanical ventilation than the control group of COVID-19 patients who did not require invasive mechanical ventilation.…”
Section: Commentmentioning
confidence: 99%